Computational studies on horseshoe shape pocket of human orexin receptor type 2 and boat conformation of suvorexant by molecular dynamics simulations - Bai, Qifeng; Pérez‐Sánchez, Horacio; Shi, Zhuoyu; Li, Lanlan; Shi, Danfeng; Liu, Huanxiang; Yao, Xiaojun (Chemical biology & drug design, 2018)
The FDA approved drug suvorexant binds to the horseshoe shape pocket of OX2R with the boat conformation. The horseshoe shape pocket plays an important role on the biological activity of OX2R in the cell membrane. To study the binding mechanism between the horseshoe shape pocket of OX2R and boat conformation of suvorexant, the crystal structures of wild type and N324A mutant of OX2R in complex with antagonist suvorexant are chosen to perform molecular dynamics (MD) simulations, QM/MM, and MMGBSA calculations. By comparison with the wild type of OX2R, the results show the 1,2,3‐triazole and p‐toluamide groups of suvorexant are changed in the N324A mutant of OX2R during 200 ns MD simulations. The QM/MM and weak interaction analysis are employed to calculate the non‐covalent bonds interaction between suvorexant and key residues in the wild type and N324A mutant of OX2R. The MMGBSA calculations indicate the entropy energy is an important influence factor for suvorexant affinity in the distorted horseshoe shape pocket of OX2R. Our results not only show the horseshoe shape pocket of OX2R is the necessary conformation for the binding of antagonist suvorexant, but also give the important sites and structural features for antagonist design of OX2R. Binding mechanism between boat conformation of suvorexant and horseshoe shape pocket of OX2R is studied. The results show the change mechanism of boat conformational suvorexant in the horseshoe shape pocket of OX2R. It supplies the structural feature information for further drug design of OX2R.